PENINGKATAN KECERDASAN VISUAL SPASIAL ANAK USIA DINI MELALUI PERMAINAN MAZELAILY ROSIDAH - ROSIDAH, LAILY (Jurnal Pendidikan Usia Dini, 2014)
This research is motivated by the lack of visual spatial ability in kindergarten children Utsmanil Judge, Land Sareal-Bogor. It is seen from them is takes of students in determining the right-left direction, recognize colors and difficulty remembering and classifying children in geometric shapes. This study aimsto improv echildren’s visual-spatial intelligence through amaze game. This research was conducted in kindergarten Utsmanil Judge, Land Sareal-Bogor with child research subjects 12 peoplein Mayand June 2014 This study used aqualitative approach to action research method. The results showed the maze games can improve children’s visual-spatial intelligence. It can be seen from the increase obtained from the firs tcycleby 33.43% on average so that thes patial intelligence of children 77.7%. While the initialconditions of the average visualspatial intelligence before the child’s actions amounted to44.27%. After the second cycle the nan increase of 7:19%, so the average value ofchildren’s visual-spatial intelligence obtained in the second cycle was 84.89%. In this study it can be concluded that thev isual-spatial intelligence can be improved through a maze game. Conducting a maze madeeveryday with avariety of different media as well as individual activities carried ou tby the group know. Keyword: Visual Spatial Intelligence, Playing Maze, Early Childhood Abstrak: Penelitian ini dilakukan, karena rendahnya kemampuan visual spasial anak di TK Utsmanil Hakim, Tanah Sareal-Bogor. Siswa belum bisa menentukan arah kanan-kiri, mengenal warna, kesulitan mengingat dan mengelompokkan bentuk geometri. Penelitian ini bertujuan untuk meningkatkan kecerdasan visual spasial anak melalui permainan maze. Penelitian ini dilakukan di TK Utsmanil Hakim, Tanah Sareal-Bogor dengan subjek penelitian 12 anak. Penelitian ini menggunakan pendekatan kualitatif dengan metode action research. Hasil penelitian menunjukkan permainan maze yang dibuat berbagai modifikasi dapat meningkatkan kecerdasan visual spasial anak. Rata-rata kecerdasan visual spasial anak pra tindakan adalah sebesar 44.27%. Peningkatan pada siklus pertama sebesar 33.43 % sehingga rata-rata kecerdasan spasial anak sebesar 77,7%. Siklus kedua terjadi peningkatan sebesar 7.19%, sehingga nilai rata-rata kecerdasan visual spasial anak yang diperoleh pada siklus kedua sebesar 84.89%. Kata kunci: Kecerdasan Visual Spasial, Permainan Maze, Anak Usia Dini